Housing affordability for households: methodological aspects and institutional factors - Tуtok, V. (Ways to Improve Construction Efficiency, 2018)
The problems related to the formation of the affordable housing market are considered. The volume of housing construction per person in Ukraine has been analyzed. The procedure for assessing the affordability of housing for the population of Kyiv is proposed. This procedure includes the analysis of statistics in the dynamics, reflecting the living conditions of the population of Ukraine and Kiev (the volume of housing per capita, the number of apartments, the volume of commissioning of housing, the indicator of indirect cost of construction of housing, average income of the population, the number of mortgages issued credits) and the calculation of special indices. The conducted statistical analysis showed the relative inaccessibility of housing for the population of Kyiv when using their own income. An analysis of the population's own incomes showed the low ability of Kyiv families to buy their own homes. In addition, the gap between the income of Kyiv's population and housing market prices continues to widen. The analysis showed that the mortgage market is steadily developing, but due to various factors (high interest rates, insufficient average income of the population, etc.), it cannot sufficiently meet the housing needs of Kyiv's population. These findings also confirm the author's housing affordability ratios: simple affordability, affordability (including household costs). The conclusion of the article is a statement about the low availability of housing in the market of Kyiv. Price is the dominant factor in assessing the affordability of housing if the rate of increase in housing prices over a period of time is higher than the rate of increase in household income. A number of recommendations are offered to improve the housing market situation and facilitate the solution of the selected problem, namely to take measures to restrain the rise in prices in the housing market, reorienting the concept of housing market development not as a consumer product market, but as a socially necessary commodity to the population.